ERGONOMIC GYMNASTIC TRAINING TO IMPROVE THE ABILITY OF ELDERLY CADRES TO REDUCE BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION - Yurike Septianingrum; Muhammad Khafid; Nety Mawarda Hatmanti; Difran Nobel Bistara; Retna Gumilang (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
The COVID-19 pandemic that lasted for two years had an impact on the health of the elderly, especially the elderly with hypertension. Elderly health development through Posyandu Lansia provides great benefits for the elderly with hypertension in controlling their blood pressure, but this activity must be vacuumed during the pandemic. The reduction in the number of COVID-19 cases is expected to be able to reactivate of Posyandu Lansia, so that elderly health cadres as activity drivers can improve their knowledge and skills. The purpose of this activity is to increase the knowledge and skills of elderly health cadres in the implementation of ergonomic gymnastics to reduce blood pressure in the elderly with hypertension. The method used in this community service activity is a participative educational approach, namely providing health education and demonstrations regarding ergonomic gymnastics. This activity was carried out for one month and was attended by ten elderly health cadres. Knowledge and skills of cadres in carrying out ergonomic gymnastics were observed with questionnaires and Standard Operating Procedures (SOP). The results of community service show that the knowledge and skills of elderly health cadres in carrying out ergonomic gymnastics are very good.